Reigniting work engagement through coping for burned-out academics: An open distance learning context - Bronwyn Wright; Linda Steyn; Annelize van Niekerk (SA Journal of Industrial Psychology)
Orientation: The South African higher education landscape is undergoing significant change because of government mandates, the post-coronavirus disease 2019 (COVID-19) pandemic and digitalisation. This has led to an increase in job demands, contributing to burnout among academics and necessitating effective coping strategies to sustain their work engagement.